THE PROBLEM OF COMIC TYPE CREATION IN O'HENRY'S WORKS - Suxrob Saitov Djumaydillayevich (American Journals, 2024)
The challenge of creating comic types in O. Henry's works frequently centers on the portrayal of characters that, in order to achieve comedic effect, display exaggerated or quirky qualities. These characters are frequently clichéd in that they represent specific archetypes or traits that are meant to be humorous. The brilliance of O. Henry's writing resides in his ability to infuse these comedic types with vivid, enduring personalities that interact in novel and entertaining ways. This article examines the complex processes involved in the creation of the comic genre in O'Henry's literary field. Through a close examination of storytelling techniques, recurring characters, and thematic patterns, we uncover the underlying mechanisms of O'Henry's comedic genius. By analyzing the structure of comic archetypes and their role in shaping narrative dynamics, we gain valuable insights into O'Henry's unique storytelling style and its lasting impact on readers.
Keywords: Storytelling techniques, characterization and archetypes, narrative techniques, social commentary.